Ungdomakriminalitet - En kvalitativ studie om risk- och skyddsfaktorer samt familjebehandlares förebyggande arbete - Harb,Mariam; Celebic,Ilda (2025)
Youth delinquency constitutes a significant social problem, both internationally and nationally. This study explored risk and protective factors that influenced youth involvement in criminal behaviour. The study was based on semi-structured interviews with eight family therapists within social services in Sweden, all of whom had experience with young men involved in youth delinquency. The analysis was guided by Travis Hirschi’s social control theory and John Bowlby’s attachment theory. The findings confirmed that youth delinquency is a multifactorial phenomenon, as supported by both the interviews and previous research. The result of this study identified key factors, such as family relationships, educational engagement, economic conditions, peer associations, and social belonging, all of which could act as either risk or protective influences. Furthermore, family therapists described family therapy efforts as focused on early intervention and collaboration, aiming to strengthen family relationships and prevent youth from entering or remaining in criminal environments.
Keywords: delinquency; risk - and protective factors; youth crime; risk factors crime; preventive factors crime